ANALISIS PERPUTARAN KAS DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PT. MULTI PRIMA SEJAHTERA, Tbk - Ersa Novry Salsabillah; Nurhayati Nurhayati (LP2M Universitas Bina Bangsa, 2022)
The capital market is a means and infrastructure of funding for companies or the government. The capital market is an activity where the sirplus of funds and the demand for funds meet through the negotiation of securities. The choice of securities to invest in are stocks, bonds, mutual funds, derivatives (options and futures). Of all the capital markets above, the most famous is stocks. The performance of a company can be reflected in cash turnover, earnings per share and financial risks that can explain management's ability to run the company. If the value of the company looks good and operates continuously with an increase, it is likely that the stock price will be higher. The purpose of this study is to determine the effect of cash turnover and earnings per share on the share price of PT. PT. Multi Prima Sejahtera, Tbk. The data used in this study is used data from PT. PT. Multi Prima Sejahtera, Tbk financial report 1990-2021 which is listed on the Indonesian stock exchange. The sample is determined by deliberate sampling so that the sample can be obtained within 10 years. The techniques used in this study were data analysis with Classical Assumption Test (Normality Test, Multicholinearity Test, Heteroskedasticity Test, Autocorrelation Test), Multiple Linear Regression Analysis, Correlation Analysis, Coefficient of Determination and Significant Test using the spss program version 26. The results of the study showed that there was no partial significant influence between cash turnover and the share price of PT. Meanwhile, Multi Prima Sejahtera, Tbk. Meanwhile, simultaneously there is a significant influence between cash turnover and earnings per share on stock prices